Size‐dependent light scattering of CoOOH nanoflakes for convenient and sensitive detection of alkaline phosphatase in human serum. (24th May 2021) - Zhu, Lu Ning; Cheng, Ru; Kang, Kai Wen; Chen, Ming Yun; Zhan, Tianrong; Wang, Jian
Abstract: As a natural enzyme, alkaline phosphatase (ALP) plays an essential role in clinicopathological examinations and biomedical research, and is capable of hydrolyzing the phosphate group of l ‐ascorbic acid‐2‐phosphate (AAP) to yield l ‐ascorbic acid (L‐AA). L‐AA reduced cobalt oxyhydroxide (CoOOH) nanoflakes to Co 2+, leading to a smaller size and weaker light scattering, which could be monitored by electron microscopic images and optical spectra. The indirect detection of ALP was achieved by the reduced light scattering signal of CoOOH nanoflakes. Under optimal conditions, the decrease in scattering intensity was proportional to the ALP concentration over the range 0.1–160 U/L and the detection limit was 0.034 U/L (3σ/ k ). Compared with other assays, this proposed light scattering method was more convenient and economic for ALP sensing. The method was successfully applied to ALP analysis in human serum samples, and was similar to the results obtained by commercial kits. Abstract : In this work, an inexpensive and simple light scattering assay was developed for the sensitive and selective detection of for ALP activity in human serum, which provides new insights into develop sensitive and convenient light scattering sensors to achieve the purpose of early diagnosis of diseases.